Analysis of dietary pattern, physical activity and medication adherence on glycemic stability among patients with type 2 diabetes mellitus - Nurwahida Nurwahida; Saimi Saimi; Akhmad Fathoni (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Diabetes is a non-communicable disease. The number of diabetes cases and the prevalence of the disease have increased continuously in recent decades. Diet and physical activity are considered to be determining factors and are closely linked to the development of diabetes. Purpose: To analyze dietary patterns, physical activity, and medication adherence to glycemic stability in a community with type 2 diabetes mellitus. Method: This quantitative study employed analytical observation with a cross-sectional approach. The population comprised all patients with type 2 diabetes mellitus in the Montong Betok Community Health Center in December 2023. Sample inclusion criteria included residents aged 40 years and above who were willing to participate and had suffered from type 2 diabetes mellitus for more than 1 year and had been taking medication according to the recommended dosage with random blood sugar levels between 100 and 400 mg/dL. Simple random sampling was used to select 199 respondents. The analysis conducted in this study included univariate analysis, bivariate chi-square with SPPS version 20 for Windows, and multivariate analysis using logistic regression test. Results: The logistic regression analysis obtained a significance level of <0.05 for the variables of diet, physical activity, and medication adherence. This indicates that diet, physical activity, and medication adherence significantly influence respondents' blood sugar stability. Of the three variables analyzed, medication adherence had the largest Exp (B) coefficient, namely 1.346. This indicates that medication adherence is the variable that most dominantly influences blood sugar stability compared to diet and physical activity. Conclusion: Eating habits, physical activity, and medication adherence have a significant impact on blood sugar stability in type 2 diabetes mellitus patients. However, medication adherence variables are an important factor that influences type 2 diabetes mellitus patients.